Neonatal exposure to aluminum chloride predisposes adult and senile gerbils to the prostatic hyperplasia - Gomes, Liana Silva; da Silva Lima, Danilo; Costa, Janaína Ribeiro; Naves, Jane Sousa; Marques, Mara Rúbia; Taboga, Sebastião Roberto [UNESP]; Ghedini, Paulo César; Biancardi, Manoel Francisco; Alcantara dos Santos, Fernanda Cristina (Wiley, 2023)
Several pollutants can alter neonatal prostatic development predisposing this gland to diseases. The toxicity and endocrine disrupting potential of aluminum has been reported in many organs, but little is known about its effects on the prostate. This study aimed to evaluate the effects that aluminum neonatal exposure can cause in the male ventral prostate and in the female prostate of adult and senile gerbils. Male and female pups were treated orally with aluminum chloride (10 mg/kg) from the 1st to the 14th day life. After treatment, the animals were aged until they reached 90 days or 1 year of life. The prostate glands were dissected out and submitted to morphological, immunohistochemical and ultrastructural analyses. Ventral prostates of adult males showed moderate hyperplasia and increased epithelial proliferation not associated with androgen receptor (AR) deregulation. On the other hand, senile males showed intense prostatic hyperplasia, and increased cell proliferation and epithelial AR regulation. Additionally, at both ages, there was a reduction in the prostate secretory function. The morphological changes observed in the female prostate were like those found in males. However, in adult females, prostatic hyperplasia was accompanied by a lower regulation of AR and estrogen receptor alpha, while in senile females, intense hyperplastic growth was associated with an increase in estrogen receptor alpha and a reduction in stromal AR. These results demonstrate that aluminum chloride neonatal exposure alters the hormonal regulation of the male and female prostate, inducing tissue damage that occurs in adulthood and intensifies during aging.
Keywords: androgens; endocrine disruptors; estrogens; female prostate; metals; ventral prostate